A structural basis for BRD2/4-mediated host chromatin interaction and oligomer assembly of Kaposi sarcoma-associated herpesvirus and murine gammaherpesvirus LANA proteins. - Jan Hellert (Public Library of Science (PLoS), 2013)
Kaposi sarcoma-associated herpesvirus (KSHV) establishes a lifelong latent infection and causes several malignancies in humans. Murine herpesvirus 68 (MHV-68) is a related γ2-herpesvirus frequently used as a model to study the biology of γ-herpesviruses in vivo. The KSHV latency-associated nuclear antigen (kLANA) and the MHV68 mLANA (orf73) protein are required for latent viral replication and persistence. Latent episomal KSHV genomes and kLANA form nuclear microdomains, termed 'LANA speckles', which also contain cellular chromatin proteins, including BRD2 and BRD4, members of the BRD/BET family of chromatin modulators. We solved the X-ray crystal structure of the C-terminal DNA binding domains (CTD) of kLANA and MHV-68 mLANA. While these structures share the overall fold with the EBNA1 protein of Epstein-Barr virus, they differ substantially in their surface characteristics. Opposite to the DNA binding site, both kLANA and mLANA CTD contain a characteristic lysine-rich positively charged surface patch, which appears to be a unique feature of γ2-herpesviral LANA proteins. Importantly, kLANA and mLANA CTD dimers undergo higher order oligomerization. Using NMR spectroscopy we identified a specific binding site for the ET domains of BRD2/4 on kLANA. Functional studies employing multiple kLANA mutants indicate that the oligomerization of native kLANA CTD dimers, the characteristic basic patch and the ET binding site on the kLANA surface are required for the formation of kLANA 'nuclear speckles' and latent replication. Similarly, the basic patch on mLANA contributes to the establishment of MHV-68 latency in spleen cells in vivo. In summary, our data provide a structural basis for the formation of higher order LANA oligomers, which is required for nuclear speckle formation, latent replication and viral persistence.